Influence of temperature variation on the reflective cracking behaviour of asphalt overlays - Minhoto, Manuel J. C. (2006)
The objective of this paper is to present a study about the influence of temperature on the reflective cracking behavior through the evaluation of the overlay damage associated to the temperature variation during the year. The development of this study war based on the numerical simulation of the overlay behaviour, based on a three-dimensional finite-element analysis, considering the simultaneous loading of traffic and temperature variation and considering the most predominant type of overlay distress observed in the field: the reflective cracking. A mechanistic-based overlay design method was used to predict the reflective cracking overlay life. The occurrence of the temperature variation in the pavements leads to an increase of the reflective cracking phenomenon, due to the stress and strain states created by the temperature, which produce the premature distress of the overlay. Thus, for overlay design purposes, it is important to consider the temperature variation in the evaluation of the overlay behaviour produced by the reflective cracking. Comparisons between expected performance of asphalt rubber hot mix, produced by the wet process with 20% crumb rubber, and conventional asphalt overlays were made, taking into account the performance of these mixes.